2021
DOI: 10.1073/pnas.2101730118
|View full text |Cite
|
Sign up to set email alerts
|

Suberin plasticity to developmental and exogenous cues is regulated by a set of MYB transcription factors

Abstract: Suberin is a hydrophobic biopolymer that can be deposited at the periphery of cells, forming protective barriers against biotic and abiotic stress. In roots, suberin forms lamellae at the periphery of endodermal cells where it plays crucial roles in the control of water and mineral transport. Suberin formation is highly regulated by developmental and environmental cues. However, the mechanisms controlling its spatiotemporal regulation are poorly understood. Here, we show that endodermal suberin is regulated in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 62 publications
9
95
2
Order By: Relevance
“…Expectedly, the corresponding Arabidopsis atsub mutant roots accumulated less suberin content compared to wild-type roots [54]. More recently, Shukla et al [51] showed that MYB41, MYB53, MYB92 and MYB93 all promote endodermal suberization in Arabidopsis roots (Figure 3). The authors mutated these four MYBs simultaneously through genome-editing tools, which led to a dramatic reduction in suberin formation in response to both developmental and environmental signals [51].…”
Section: Regulation Of the Suberin Pathwaymentioning
confidence: 93%
“…Expectedly, the corresponding Arabidopsis atsub mutant roots accumulated less suberin content compared to wild-type roots [54]. More recently, Shukla et al [51] showed that MYB41, MYB53, MYB92 and MYB93 all promote endodermal suberization in Arabidopsis roots (Figure 3). The authors mutated these four MYBs simultaneously through genome-editing tools, which led to a dramatic reduction in suberin formation in response to both developmental and environmental signals [51].…”
Section: Regulation Of the Suberin Pathwaymentioning
confidence: 93%
“…Therefore, we investigated their suberin composition and lamellae structure. Of note, a recent study reported the suberin composition of myb41 myb53 myb92 myb93, a quadruple mutant that shows an overall ~78% decrease in suberin monomers compared to the wild type [30].…”
Section: Cyp86a1-1 Cyp86b1-1 Has Reduced Total Suberin Content and Ultrastructural Defectsmentioning
confidence: 99%
“…Compared to the wild type, esb1 has higher water-use efficiency (WUE) and a lower transpiration rate associated with enhanced suberin deposition in roots [28]. Conversely, suberin-deficient mutants show susceptibility to salt stress [24,29,30]. In a recent study, suberin deposition was characterized through development and found to be upregulated under water-deficit conditions in grapevine roots [31].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that exogenous application of ABA induces the expression of suberin-related genes and increases suberin deposition in the endodermis, while triggering ectopic suberin deposition in root tips and in potato tubers [ 76 , 154 , 155 , 156 , 157 , 158 , 159 ]. An essential role of basal ABA in endodermal suberization has been supported by genetic studies.…”
Section: Role Of Aba In Plant Developmentmentioning
confidence: 99%
“…ABA-dependent suberin deposition is mediated by MYB41-MYB53-MYB92-MYB93 , which are expressed in the endodermis and induced by ABA. A quadruple myb41 myb53 myb92 myb93 mutant shows a nearly complete lack of endodermal root suberin, which could not be rescued by application of ABA [ 159 ], whereas overexpression of some MYB TFs results in ectopic suberin accumulation [ 156 , 160 ] ( Figure 2 ). ABA-induced suberin deposition also requires the auxin-regulated GDSL lipases, some of which have been proposed to be involved in suberin degradation while other in ABA-mediated suberin synthesis [ 159 ].…”
Section: Role Of Aba In Plant Developmentmentioning
confidence: 99%